Igualdad de derechos de las uniones de hecho y la familia matrimonial en asociaciones - Romero Antola, Mario (2019)
The equality of marital and extramarital relations is the subject of extensive discussion. This paper analyzes this phenomenon in terms of equal rights and obligations within associations with respect to the wife or husband of associate and the concubines